2018
DOI: 10.3389/fphar.2018.01302
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Effects of Triterpenoid Saponins From Stauntonia chinensis via Selective Increase in Inhibitory Synaptic Response in Mouse Cortical Neurons

Abstract: Triterpenoid saponins from Stauntonia chinensis (TSS) are potential therapeutic agents because of its analgesic properties. However, the underlying mechanisms of the anti-nociceptive activity of TSS are largely unclear, especially in CNS. The present study confirmed the analgesic effect of TSS using four models of acute pain based on thermal or chemical stimuli. TSS treatment specifically impaired the threshold of thermal- and chemical-stimulated acute pain. Naloxone did not block the anti-nociceptive effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 43 publications
(44 reference statements)
2
24
0
Order By: Relevance
“…For example, total saponins of Psammosilene tunicoids inhibited algesia threshold and effectively decreased the contents of MDA, IL-1β, and TNF-α in the inflammatory tissue soak of rats with adjuvant-induced arthritis [ 17 , 18 ]. The triterpenoid saponins from Stauntonia chinensis enhanced the threshold of thermal- and chemical-stimulated acute pain, which directly increased the inhibitory synaptic response in mouse cortex neurons at the resting state [ 19 ]. P. stipuleanatus was traditionally used to treat pain-related diseases.…”
Section: Resultsmentioning
confidence: 99%
“…For example, total saponins of Psammosilene tunicoids inhibited algesia threshold and effectively decreased the contents of MDA, IL-1β, and TNF-α in the inflammatory tissue soak of rats with adjuvant-induced arthritis [ 17 , 18 ]. The triterpenoid saponins from Stauntonia chinensis enhanced the threshold of thermal- and chemical-stimulated acute pain, which directly increased the inhibitory synaptic response in mouse cortex neurons at the resting state [ 19 ]. P. stipuleanatus was traditionally used to treat pain-related diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Other reports indicated that quercetin produce anti-inflammatory action in mouse models of colitis, periodontitis, cancer pain, and acute pain via exertion of the inhibitory effect on neutrophil recruitments, oxidative stress, and COX-2 [ 42 44 ]. Also, saponin containing plant such as Stauntonia chinensis has been reported to demonstrate significant analgesia in the mouse hot plate, acetic acid-induced writhing, formalin, and capsaicin tests through elevation of the inhibitory synaptic response in cortical neurons [ 45 ]. Therefore, the presence of flavonoids, phenolic compounds, and saponins in THBE may contribute to its profound attenuation of acute nociceptive and inflammatory pain in this study.…”
Section: Discussionmentioning
confidence: 99%
“…44,45 Triterpenic saponins also exhibit antioxidant and anti-inflammatory properties. 46,47 A greater antioxidant and anti-inflammatory activity were observed for the leaf extract, which presented the highest concentration of phenols and flavonoids. It has been shown that these metabolites can contribute directly to the activities previously described.…”
Section: Antioxidant Activitiesmentioning
confidence: 96%